Advanced Sensing and Safety Control for Connected and Automated Vehicles - Huang, Chao; Wang, Yafei; Hang, Peng; Zuo, Zhiqiang; Leng, Bo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The connected and automated vehicle (CAV) is a promising piece of technology, anticipated to enhance the safety and effectiveness of mobility. Advanced sensing technologies and control algorithms, working to acquire environmental data, analyze data, and regulate vehicle movements, are key functional components of CAVs. In recent years, the creation of innovative sensing technologies for CAVs has gained substantial attention. CAVs can now interpret sensory data to more accurately detect impediments, track their locations, navigate autonomously in a dynamic environment, and communicate with other nearby vehicles. This has been made possible by advancements in sensing technology. Additionally, by utilizing computer vision and other sensing techniques, the bodily movements, facial expressions, and even mental states of in-cabin persons can be identified.